Advances in sorghum improvement for climate resilience in the global arid and semi-arid tropics: A Review - Mwamahonje, Andekelile; Mdindikasi, Zamu; Mchau, Devotha; Mwenda. Emmanuel; Sanga, Daines; Garcia Oliveira, Ana Luísa; Ojiewo, Chris O. (MDPI, 2024)
Sorghum is a climate-resilient crop which has been cultivated as a staple food in the semi-arid areas of Africa and Asia for food and nutrition security. However, the current climate change is increasingly affecting sorghum performance, especially at the flowering stage when water availability is critical for grain filling, thus lowering the sorghum grain yield. The development of climate-resilient, biotic and abiotic stress-tolerant, market-preferred, and nutrient-dense sorghum varieties offers a potentially cost-effective and environmentally sustainable strategy for adapting to climate change. Some of the common technologies for sorghum improvement include mass selection, single seed descent, pure line selection, and marker-assisted selection, facilitated by backcrossing and genotyping using molecular markers. In addition, recent advancements including new machine learning algorithms, gene editing, genomic selection, rapid generation advancement, and recycling of elite material, along with high-throughput phenotyping tools such as drone- and satellite-based images and other speed-breeding techniques, have increased the precision, speed, and accuracy of new crop variety development. In addition to these modern breeding tools and technologies, enhancing genetic diversity to incorporate various climate resilience traits, including against heat and drought stress, into the current sorghum breeding pools is critical. This review covers the potential of sorghum as a staple food crop, explores the genetic diversity of sorghum, discusses the challenges facing sorghum breeding, highlights the recent advancements in technologies for sorghum breeding, and addresses the perceptions of farmers on sorghum production under the current climate change conditions.